2016
DOI: 10.1021/acs.nanolett.5b03504
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Perovskite Thin Films into Nanowires with Kinetic Control for Flexible Optoelectronic Devices

Abstract: With significant progress in the past decade, semiconductor nanowires have demonstrated unique features compared to their thin film counterparts, such as enhanced light absorption, mechanical integrity and reduced therma conductivity, etc. However, technologies of semiconductor thin film still serve as foundations of several major industries, such as electronics, displays, energy, etc. A direct path to convert thin film to nanowires can build a bridge between these two and therefore facilitate the large-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
138
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(145 citation statements)
references
References 42 publications
7
138
0
Order By: Relevance
“…Several fabrication techniques have been developed for the growth of organic-− inorganic perovskite nanowires (NWs) directly 58 Yuan et al 59 reported deep blue-luminescent layered lead bromide perovskite microdisks, a few micrometers in size laterally and 15-100 nm-thick with a PLQY reaching 50%. The same group also reported nanoscale quasi-2D layered perovskites with tunable emissions from 403 to 530 nm by changing the organic cations used.…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
“…Several fabrication techniques have been developed for the growth of organic-− inorganic perovskite nanowires (NWs) directly 58 Yuan et al 59 reported deep blue-luminescent layered lead bromide perovskite microdisks, a few micrometers in size laterally and 15-100 nm-thick with a PLQY reaching 50%. The same group also reported nanoscale quasi-2D layered perovskites with tunable emissions from 403 to 530 nm by changing the organic cations used.…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
“…Hybrid perovskites have attracted great interest due to their tunable bandgaps and superior energy conversion properties. The bangap tuning were generally implemented by changing the composition by halogen anion [10][11][12][13][14] or cation [15][16][17] Nowadays, the synthesis methods of perovskite NWs were ascribed to solvent evaporation assisted self-assembly method [19][20][21][22][23][24] . And most reports utilized organic polar solvent such as N, N-dimethyformamide (DMF), dimethyl sulfoxide(DMSO) in solution method.…”
Section: Introductionmentioning
confidence: 99%
“…A thin saturated solution film of MAPbI 3 in DMF was confined by two glass slides, and the nanowires came into crystallization while gradually sliding the upper glass to expose the liquid to air. It was assumed that the nanowire growth was due to the directional effect of DMF that an internal complex with the methylamine group was formed during the crystallization process . A great breakthrough in halide perovskite nanowire synthesis was put forward by Fu et al (Figure J) They proposed a dissolution‐recrystallization model to grow single‐crystalline MAPbI 3 nanowires.…”
Section: D Metal Halide Perovskitesmentioning
confidence: 99%
“…The inset is the photograph of the flexible detector. Reproduced with permission . Copyright 2016 American Chemical Society.…”
Section: D Metal Halide Perovskitesmentioning
confidence: 99%